Reevaluating the Grammar Translation Method: Its Effectiveness in Enhancing Interactional Speaking Skills of Junior High School Students - Kaharuddin, Kaharuddin (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The English curriculum at the junior high school level in Indonesia requires students to have interactive speaking skills in both formal and informal contexts. However, in reality, many students still have difficulty speaking accurately and coherently, especially in oral interactions. This study aims to analyze the effect of the Grammar Translation Method (GTM) on the interactive speaking skills of eighth-grade students and to compare the effectiveness of GTM with Communicative Language Teaching (CLT). This study uses a quasi-experimental design with a pre-test–post-test control group pattern. The research sample consisted of 60 eighth-grade students from two classes taught using GTM and CLT. Data were collected through dialogue-based speaking performance tests and analyzed using paired sample t-tests and independent sample t-tests. The results showed that students taught using GTM experienced a more significant improvement in grammatical accuracy, vocabulary mastery, and interactional strategies, while CLT students excelled in speaking fluency. These findings indicate that GTM is still relevant and effective as a supporting method in the development of interactive speaking skills, especially when combined with a communicative approach.